2021
DOI: 10.1016/j.ejca.2021.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of circulating tumour DNA to identify patients with epidermal growth factor receptor–positive non-small cell lung cancer who might benefit from sequential tyrosine kinase inhibitor treatment

Abstract: Background: Survival data support the use of first-line osimertinib as the standard of care for epidermal growth factor receptor (EGFR)epositive non-small cell lung cancer (NSCLC). However, it remains unclear whether upfront osimertinib is superior to sequential first-or second-generation tyrosine kinase inhibitors (TKIs) followed by osimertinib for all patients. It is impossible to predict which patients are at high risk of progression, and this constitutes a major limitation of the sequential TKI approach. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…The CT imaging has been clinically utilized for response assessment but with limited concordance with pathologic response (10,11). Change of ctDNA was shown to be predictive for treatment efficacy in advanced cancers (20)(21)(22)(23). In locally advanced, unresectable, NSCLC ctDNA has been shown to predict survival outcomes (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CT imaging has been clinically utilized for response assessment but with limited concordance with pathologic response (10,11). Change of ctDNA was shown to be predictive for treatment efficacy in advanced cancers (20)(21)(22)(23). In locally advanced, unresectable, NSCLC ctDNA has been shown to predict survival outcomes (35).…”
Section: Discussionmentioning
confidence: 99%
“…In several cancers, including lung cancer, bladder cancer, and colorectal cancer, ctDNAbased profiling following surgery has shown encouraging performance in revealing MRD (16)(17)(18)(19). In addition, ctDNA clearance has been shown to pose correlations with better treatment efficacy in advanced cancers (20)(21)(22)(23), based on which its' effects in evaluating the efficacy of neoadjuvant therapy (NAT) have also been exploited. In bladder cancers, ctDNA has been found to be correlated with response to NAT (24).…”
Section: Introductionmentioning
confidence: 99%
“…Given that this group of patients would have a better prognosis at the beginning and a lower hazard of death, it is in this group that we could carry out a study to sequence different TKIs (1st, 2nd and 3rd generation) and chemotherapy. There are various liquid biopsy studies [ 33 ] that have observed that, depending on the allelic frequency of the mutation (MAF), it is possible to identify low-risk patients who could be candidates for sequential treatment. In comparison, patients at a higher risk of death would be those who would benefit the most from starting first-line osimertinib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of circulating tumor DNA (ctDNA) has become an attractive approach for non-invasive biomarker testing as well as for real-time monitoring of cancer patients; its usefulness is especially remarkable in lung cancer patients [1][2][3][4]. These tumors are Biology 2021, 10, 954 2 of 10 mostly diagnosed at advanced stages, in elderly patients with a median age at diagnosis of approximately 65 years [5], and they are difficult to access owing to their anatomical location, which makes it sometimes difficult to obtain sufficient material for molecular analysis [6]. Moreover, in the last decades, there has been a major paradigm shift in the management of metastatic non-small cell lung cancer (NSCLC), with the advent of targeted therapies for patients harbouring druggable alterations such as EGFR or BRAF mutations, as well as ALK, ROS, and RET rearrangements, and so on [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, guidelines recommend testing for the T790M EGFR mutation in the blood after progression to an EGFR TKI as a first choice, and re-biopsies are suggested in the case of a negative result in order to identify patients that can benefit from osimertinib (a third-generation TKI) [11]. Moreover, ctDNA plasma levels have been shown to be of prognostic significance for these patients, and monitoring EGFR mutation levels in the plasmas has been proven useful for response to treatment monitoring [5,12,13].…”
Section: Introductionmentioning
confidence: 99%